Are newly introduced criteria for the diagnosis of gestational diabetes mellitus associated with improved pregnancy outcomes and/or increased interventions in New South Wales, Australia? A population-based data linkage study. Issue 1 (28th June 2021) - Randall, Deborah A; Morris, Jonathan M; Kelly, Patrick; Glastras, Sarah J
Abstract : Introduction: The incidence of gestational diabetes mellitus (GDM) is increasing in Australia, influenced by changed diagnostic criteria. We aimed to identify whether the diagnostic change was associated with improved outcomes and/or increased obstetric interventions using state-wide data in New South Wales (NSW), Australia. Research design and methods: Perinatal and hospital data were linked for singleton births, 33–41 weeks' gestation, 2006–2015, NSW. An adjusted Poisson model was used to split pregnancies from 2011 onwards into those that would have been diagnosed under the old criteria ('previous GDM') and newly diagnosed cases ('additional GDM'). We compared actual rates of total and early (<39 weeks) planned births, cesareans, and maternal and neonatal adverse outcomes for GDM-diagnosed pregnancies using three predicted scenarios, where the 'additional GDM' group was assumed to have the same rates as: the 'previous GDM' group <2011 (scenario A); the 'non-GDM' group <2011 (scenario B); or the 'non-GDM' group ≥2011 (scenario C). Results: GDM incidence more than doubled over the study period, with an inflection point observed at 2011. For those diagnosed with GDM since 2011, the actual incidence of interventions (planned births and cesareans) and macrosomia was consistent with scenario A, which meant higher intervention rates, but lower rates of macrosomia, than those with no GDM. Incidence of neonatal hypoglycemia was lower than scenario A and closer to the other scenarios. There was a reduction in perinatal deaths among those with GDM, lower than that predicted by all scenarios, indicating an improvement for all with GDM, not only women newly diagnosed. Incidence of maternal and neonatal morbidity indicators was within the confidence bounds for all three predicted scenarios. Conclusions: Our study suggests that the widely adopted new diagnostic criteria for GDM are associated with increased obstetric intervention rates and lower rates of macrosomic babies, but with no clear impacts on maternal or neonatal morbidity.